Temporary Territories and Persistent Places: A Bioarchaeological Evaluation of the Association between Monumentality and Territoriality for Foraging Societies of the Prehistoric Ohio Valley - Seidel, Andrew Colin; Carr, Christopher; Stojanowski, Christopher M; Buikstra, Jane E; Aguilera, Miguel (Temporary Territories and Persistent Places: A Bioarchaeological Evaluation of the Association between Monumentality and Territoriality for Foraging Societies of the Prehistoric Ohio Valley)
Federal legislation prioritizes the repatriation of culturally unidentifiable human remains to federally-recognized Indian tribes that are linked geographically to the region from which the remains were removed. Such linkages are typically based on a Eurocentric notion of the exclusive use and occupancy of an area of land - a space-based approach to land use. Contemporary collaborations between anthropologists and indigenous communities suggest, however, that indigenous patterns of land use are better characterized as place-based and are therefore more complex and fluid than is reflected in current legislation. Despite these insights, space-based approaches remain common within archaeology. One example is the inference of territorial behavior from the presence of monuments within the archaeological record. Drawing on osteological and mortuary data derived from a sample of Adena mounds located in northern Kentucky, this dissertation adopts a place-based approach in order to evaluate the archaeological association between monumentality and territoriality. The relative amounts of skeletal and phenotypic variability present at various spatial scales are quantified and compared and the degree to which mortuary and phenotypic data exhibit spatial structure consistent with the expectations of an isolation-by-distance model is assessed. Results indicate that, while burial samples derived from some mounds exhibit amounts of phenotypic variability that are consistent with the expectations of a territorial model, data from other mounds suggest that multiple groups participated in their construction. Further, the general absence of spatial structure within the phenotypic data suggests that the individuals interred in these mounds are perhaps better characterized as representing an integrated regional population rather than localized groups. Untested archaeological inferences of territoriality may therefore mischaracterize regional population dynamics. In addition, these results suggest that the prioritization criteria for the repatriation of culturally unidentifiable human remains may merit revision.
Doctoral Dissertation Anthropology 2019
Keywords: Adena; Archaeology; Biodistance; Kentucky; Mortuary Practices; Physical anthropology